Studying Deformations of Fuchsian Representations with Higgs Bundles - Collier, B. (Symmetry, Integrability and Geometry: Methods and Applications, 2019)
This is a survey article whose main goal is to explain how many components of the character variety of a closed surface are either deformation spaces of representations into the maximal compact subgroup or deformation spaces of certain Fuchsian representations. This latter family is of particular interest and is related to the field of higher Teichmüller theory. Our main tool is the theory of Higgs bundles. We try to develop the general theory of Higgs bundles for real groups and indicate where subtleties arise. However, the main emphasis is placed on concrete examples, which are our motivating objects. In particular, we do not prove any of the foundational theorems; rather, we state them and show how they can be used to prove interesting statements about components of the character variety. We have also not spent any time developing the tools (harmonic maps) that define the bridge between Higgs bundles and the character variety. For this side of the story, we refer the reader to the survey article of Q. Li [arXiv:1809.05747].